Z recepcji rosyjskiej literatury postmodernistycznej w Polsce (na przykładzie twórczości Władimira Sorokina, Wiktora Jerofiejewa i Wiktora Pielewina) - Szymczak, Grzegorz (Acta Polono-Ruthenica, 2018)
The article is devoted to particular issues of reception of Russian postmodern literature in Poland on examples of works by Vladimir Sorokin, Viktor Yerofeyev and Viktor Pelevin. The article discusses the successive stages of reception of prose and essays by these three writers. The aim of the paper is to define also literary and non-literary reasons for the popularity of the postmodernists in Poland.